Gender Equity in Islamic Marriage and Divorce: A Narrative Review - Lestari, Putri Ayu (Sinergi International Journal of Islamic Studies, 2024)
This narrative review examines the evolving landscape of marriage and divorce in Islamic contexts, with a focus on gender equity, legal interpretation, and socio-cultural influences. The study aims to understand the systemic barriers faced by women in initiating divorce and how legal, educational, and institutional reforms can address these challenges. Utilizing sources from Scopus, Google Scholar, JSTOR, and SpringerLink, the review analyzed literature published over the past fifteen years using keywords such as "Islamic marriage," "Islamic divorce," "fiqh," and "gender equity in Islam." The findings reveal that women often face legal and social obstacles in accessing divorce, compounded by economic dependency, limited legal knowledge, and gender-biased interpretations of Islamic law. Studies highlight the impact of educational interventions like fiqh munakahat, feminist legal reinterpretation, and national policy reforms in improving women's rights. Examples from India, Morocco, and Malaysia illustrate how legal innovation and inclusive practices can promote gender justice. The discussion emphasizes the need for systemic reforms that include educational restructuring, economic support, and protective legislation against domestic violence. In conclusion, the review advocates for context-sensitive and justice-centered reforms in Islamic family law. Emphasis is placed on legal empowerment, economic equity, and gender-sensitive interpretation of Sharia to support more equitable marital outcomes. Future research should expand in scope and methodology to ensure broader applicability and sustained social impact.